2018
DOI: 10.3126/jdean.v1i1.21188
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Prescription Pattern among Type 2 DM patients visiting Outpatient Department at a Tertiary Hospital in Kathmandu, Nepal

Abstract: Background: Management of Type 2 Diabetes Mellitus includes nonpharmacological and pharmacological interventions of which insulin remains one of the most effective methods for achieving glycemic control, either alone or in combination with oral anti-diabetic medications. Effective usage of insulin in the management of glycaemia remains a challenge in developing countries like Nepal. To best of our knowledge, there is not any study regarding insulin prescription pattern on Type 2 Diabetes Mellitus patients usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…This was confirmed in this study as well as the study by Baruah et al 15 A similar finding was seen in a study done in Nepal. 17 Human insulin was prescribed in 58.96% of individuals in the large Indian cohort while 35.7% were on analogue insulin, which is in line with the findings of this study. 15 This could be either be due to the patients' preference to continue on a medication they are already well-versed with or the prescribing physician's uncertainty in the mentality of old patients to accept the change from human to analogue without errors.…”
Section: Discussionsupporting
confidence: 90%
“…This was confirmed in this study as well as the study by Baruah et al 15 A similar finding was seen in a study done in Nepal. 17 Human insulin was prescribed in 58.96% of individuals in the large Indian cohort while 35.7% were on analogue insulin, which is in line with the findings of this study. 15 This could be either be due to the patients' preference to continue on a medication they are already well-versed with or the prescribing physician's uncertainty in the mentality of old patients to accept the change from human to analogue without errors.…”
Section: Discussionsupporting
confidence: 90%
“…Most studies on insulin use focused on between-class variation (i.e. comparison with the use of rapid-acting insulins and premixed insulins) rather than the in-between class variation (19)(20)(21)(22)(23)(24)(25). A recent analysis from the United Kingdom showed that prescription rates of long-acting insulins increased between 2003 and 2018, while prescription rates of NPH-insulin decreased.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Diabetes Mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia due to defective insulin action, insufficient insulin secretion, or both, resulting in disturbances in carbohydrate, fat, and protein metabolism. It is a global health concern with a significant burden, particularly in developing countries where it is estimated that over 70% of diabetic patients will reside by 2030 (1). The prevalence and impact of DM are profound; in Islamabad/Rawalpindi alone, 943,845 adults are affected, constituting a considerable percentage of the total population of approximately 35,350,000 as reported by the International Diabetic Federation in 2023 (3).…”
Section: Introductionmentioning
confidence: 99%